2019
DOI: 10.14744/tjtes.2019.31967
|View full text |Cite
|
Sign up to set email alerts
|

Non-operative Management of Perforated Peptic Ulcer: A Single Center Experience

Abstract: BACKGROUND: Perforation is a rare complication of peptic ulcer. Although the most widely accepted treatment for peptic ulcer perforation is surgery, non-operative treatment can be an option in selected patients. In this study, we aimed to present our non-surgical treatment experience in peptic ulcer perforation. METHODS: In this study, the data of the patients who were treated due to peptic ulcer perforation between January 2012 and September 2017 in our clinic were retrospectively reviewed. The diagnosis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…Studies included in our review are to help identifying best evidence practice for patients with PPU. Karabulut et al [ 14 ] in their retrospective study with 41 patients demonstrated that the length of stay was similar in patients treated with conservative or surgical management. Conservative approach was suggested for patient with normal vital parameters and no signs of generalised peritonitis, while surgical treatment was for patients demonstrating sins of sepsis and peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies included in our review are to help identifying best evidence practice for patients with PPU. Karabulut et al [ 14 ] in their retrospective study with 41 patients demonstrated that the length of stay was similar in patients treated with conservative or surgical management. Conservative approach was suggested for patient with normal vital parameters and no signs of generalised peritonitis, while surgical treatment was for patients demonstrating sins of sepsis and peritonitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is normally indicated in high-risk patients like those with a Boey score of 3, an ASA score of 4 or 5 and patients with multiple co-morbidities. The mortality is high in this patient and most studies have shown that this is a stop gap measure and is not widely practiced [56][57][58][59][60].…”
Section: Conservative Treatment Of Perforated Peptic Ulcermentioning
confidence: 99%